Facilitating higher photovoltaic penetration in residential distribution networks using demand side management and active voltage control. Issue 10 (4th May 2021) - Pillai, Gobind; Allison, Michael; Tun, Thet Paing; Chandrakumar Jyothi, Kiran; Kollonoor Babu, Eaby
Abstract: Future power networks are certain to have high penetrations of renewable distributed generation such as photovoltaics (PV). At times of high PV generation and low customer demand (e.g., summer), network voltage is likely to rise beyond limits mandated by grid codes resulting in a curtailment of PV generation, unless appropriate control means are used. This leads to a reduction in energy yield and consequently reduces the economic viability of PV systems. This work focuses on scenario‐based impact assessments underpinned by a net prosumer load forecasting framework as part of power system planning to aid sustainable energy policymaking. Based on use‐case scenarios, the efficacy of smart grid solutions demand side management (DSM) and Active Voltage Control in maximizing PV energy yield and therefore revenue returns for prosumers and avoided costs for distribution networks between a developed country (the UK) and developing country (India) is analyzed. The results showed that while DSM could be a preferred means because of its potential for deployment via holistic demand response schemes for India and similar developing nations, technically the combination of the weaker low voltage network with significantly higher solar resource meant that it is not effective in preventing PV energy curtailment. Abstract : This paper demonstrates that, while smart grid solutions are capable of enabling PV generation maximization and improving penetration levels, the extent of such benefits are location‐specific and are affected by the distribution network structure. Active voltage control and demand side management by load shifting were the two smart grid solutions considered.